Evidence of the Impact of EVA on the Indian Automotive Industry - P.Verma, Bigyan (Indian Journal of Finance, 2022)
This research paper examined evidence of economic value added (EV A) and its impact on and relevance in the Indian automobile industry . For that, the economic data of six NSE-listed automobile companies from 2016–17 to 2020–21 were utilized. In the analysis, the dependent variable is the log number of stock prices, and the independent variables are a log of EVA, T obin’s Q, and return on assets (ROA). In addition, an OLS regression econometric model was used to determine whether or not the independent variables explained the dependent variable in a statistically significant manner. The analysis showed a very high statistical significance at both levels ; the overall regression model and individual coefficient levels, as seen from their p-values. This outcome cemented the view that EV Ais not to be discounted in the Indian automotive sector and that it positively affected the stock price. With multiple challenges of the 21st century , disruptive technologies, and structural issues of supply and demand transformations, automotive companies would do well if they operated with EVA as their key performance measure. Moreover, new sustainable products, such as launching electric vehicles (EVs), might become a game-changer for many automotive firms in the coming years. This may benefit the growing value-sensitive market sentiments by bolstering sustainable practices of players in this sector.